EDUCAÇÃO EM SAÚDE SEXUAL DE ADOLESCENTES ESCOLARES MEDIADO POR JOGOS DIGITAIS - Cherobini, Márcia Dal Bem (2021)
Introduction: Sexual health education to prevent adolescent pregnancy is a political, social, economic and educational challenge. Adolescent pregnancy is a global public health concern as it significantly affects maternal and child health. Objectives: to know the educational strategies performed by the school and the primary attention health team at sex education in the adolescent pregnancy context and to produce a digital game for sexual health education for school adolescents. Methodology: research of qualitative approach, exploratory and descriptive. Data collection was realized through a remote interview semi-structured on the Google Meet platform, with questions about the characterization of participants and open questions directed to health education strategies developed with adolescents at school. Thirteen education professionals who work directly with adolescents and three Primary Health Care professionals responsible for developing health education at school participated in the study. The analysis and interpretation followed concepts of thematic analysis proposed by Bardin. Concerning the construction of the digital game, it was anchored methodologically on developing stages proposed by Heather Maxwell Chandler, in four steps: pre-production, production, testing, and post-production. Researchers, the technical team, the primary care health team, and teachers participated in the construction of the digital game of the “Towers Defense” genre. The graphic art was made in Procreate and vectorized in Adobe Illustrator, soundtrack and sound effects were downloaded from copyright or made in Reaper. Results: after data analysis inherent to the research, three thematic categories emerged: Lack of knowledge about the PSE strategy; Methodologies for preventing adolescent pregnancy and sex education; perspectives of health education for adolescents. The results demonstrate the relevance of strategic actions linked between education and health and implement active methodologies that help these two sectors in guidelines on sexual health and prevention of adolescent pregnancy. Based on the result mentioned and corroborating with active methodologies that trigger reflection on the theme with the adolescent audience, an Educational technology was created in form of a digital game called “Defense Towers: Adolescent Health” with two games: The Tower Defense 1: Contraceptive Methods and Sexually Transmitted Infections (STI’s) and Tower Defense 2: Hygiene of the Body in Puberty. The technology was developed after the field research, thus the educational objective, narrative, dynamic, and aesthetic were outlined and adequate to the researched reality theoretically supported by scientific evidence. Hence as a technical/technological product considering its nature, digital games are classified according to Capes Technical Production Qualis, item 2 Didactic Material T1=100 points. The digital game “Defense Towers: Adolescent Health” is relevant in the context of health education as it will enable significant learning, the building of knowledge and autonomy for adolescents in the aspect of sexual and reproductive, aiming to prevent unplanned pregnancy and STI’s. Thus, as the game is configured as Software for educational purposes, it will have applicability concerning education for sexuality in adolescence and will be monitored monthly by the triad of researchers, educators, and health professionals regarding its use. Final considerations: the game would be able to establish or strengthen bonds between adolescents, school, and city health team, as it is an articulating technology that links education and health. The game utilization as an active teaching and learning methodology will provide another strategy/tool to be used by teachers and health professionals to discuss, reflect and guide about adolescent sexuality and its interfaces.